The Analysis of Environmentally Friendliness Level of Collapsible Traps in Tambakoso, Sidoarjo Regency - Muhammad Najmi Habibi (Hasanuddin University, 2025)
Sustainable fisheries are an essential agenda in Indonesia’s capture fisheries sector to ensure future fish availability, preserve ecosystems, and maintain fishermen’s livelihoods. One approach to achieving sustainable fisheries is through the application of the Code of Conduct for Responsible Fisheries (CCRF), which serves as a framework for assessing whether capture fisheries activities are environmentally friendly and capable of supporting sustainability. This study aims to evaluate the environmental friendliness of fishing gear used by fishermen in Tambakoso Village, Sidoarjo Regency. Data were collected through direct observation and interviews with 11 fishermen operating collapsible traps (bubu lipat) targeting tiger snail (Babylonia spirata). Using a mixed-methods approach and nine principles of the CCRF, the results indicate that the collapsible trap fishing gear used by fishermen in Tambakoso Village is classified as highly environmentally friendly, achieving a total score of 30.8 points.